The Evolution of Data Engineering: Meeting Modern Regulatory Demands through Technology - Amarnath Reddy Chandra, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the intersection of emerging technologies and regulatory compliance in modern data engineering practices. The article examines how organizations are leveraging advanced technologies to meet increasingly complex regulatory requirements while maintaining operational efficiency. It explores the implementation of real-time compliance monitoring systems, blockchain integration, and federated learning across various regulated industries, particularly in financial services and healthcare sectors. The article also addresses practical implementation considerations, including technical infrastructure requirements, integration challenges, and risk management protocols. Through analysis of multiple industry studies and research findings, the article demonstrates how technological innovation is transforming regulatory compliance practices while enabling secure data sharing and cross-organizational collaboration.
Keywords: AI-driven compliance solutions; Blockchain Technology; Data Engineering; Federated Learning; Regulatory Compliance; Risk Management